(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the specifics of the verbal, non-verbal and linguistic attributes of the speech genre of expressing gratitude. At the same time, such features as the specifics of oral and written speech in the textual compositional structure of expressing gratitude, dialogic and monological, individual and collective features are highlighted. The national and cultural features of the verbal, non-verbal and linguistic attributes of the gratitude speech genre are highlighted.